The cruell subtilty of ambition discovered in a discourse concerning the King of Spaines surprizing the Valteline / Written in Italian by the author of the History of the Council of Trent. Translated by the renowned Sir Thomas Rowe, Knight, many times Ambr in forraine parts, with his epistle to the Ho. of Commons in Parliament. Showing the onely way in policie to counterplot the designes of promoting unjust interests of state. It being the same published by the Author in his lifetime. [electronic resource] :
Summary goes here